The Process of Creating Batik Motifs Based on The Bujangga Manik Script: Tradition Space Perspective - Darmayanti, Tessa Eka; pandanwangi, ariesa; ratnadewi (Institut Seni Indonesia Padangpanjang, 2024)
Massive boundaries such as walls are no longer synonymous with understanding space because space can be born from various processes or activities that are taking place. Just like the creative process of old manuscripts related to culture and history can create space. Therefore, this qualitative research aims to present an alternative perspective on space formation associated with the experience of the creative process of making Bogor batik motifs based on the Bujangga Manik manuscript. A phenomenological approach with descriptive presentation is applied to research discussions which are strengthened by the space and the creative process theories. This study reveals what form the creative and cultural space in the process of making batik motifs, namely tangible components such as creative stages that guide the transformation of written cultural texts into sketches, and intangible elements, namely the meaning of batik motifs based on Bujangga Manik Manuscript. This research contributes to Indonesian creativity and traditions in cultural products to a wide audience.